Performance of Gram Stain, Leukocyte Esterase, and Nitrite in Predicting the Presence of Urinary Tract Infections: A Diagnostic Accuracy Study - Solorzano, Carlos; Rubio, Maria Camila; Licht Ardila, Maricel; Castillo, Camila; Valencia Silva, Juan Camilo; Caro, Maria Alejandra; Manrique Hernandez, Edgar Fabian; Hurtado-Ortiz, Alexandra; Torcoroma García, Liliana (Archives of Academic Emergency Medicine, 2025)
Introduction: While urine culture is the gold standard for the urinary tract infection (UTI) diagnosis, delays in results highlight the need for rapid tests. This study aimed to evaluate the accuracy of urine Gram staining, leukocyte esterase, and nitrite in predicting the presence of UTI. Methods: A cross-sectional diagnostic accuracy study was conducted on adult patients undergoing urine culture at a high-complexity hospital in northeastern Colombia. The results of Gram staining and urinalysis (nitrite and leukocyte esterase) were compared to urine culture as the gold standard test, and screening performance characteristics were calculated and reported for individual and combined tests. Results: A total of 2,123 urine cultures were analyzed, with 49.8% testing positive. Escherichia coli was the most common pathogen (24.7%), and 76.17% of patients received antibiotics, primarily ceftriaxone (38.7%). Gram staining showed 56.9% (95% confidence interval (CI)=54.4 to 59.4) sensitivity and 76.8% (95% CI=72.6 to 80.5) specificity, leukocyte esterase had 67.9% (95% CI= 65.3 to 70.4) sensitivity and 84.5% (95% CI=81.4 to 87.2) specificity, and nitrite demonstrated the highest sensitivity (85.3%, 95% CI=82.0 to 88.2). The combination of Gram staining (+), leukocyte esterase (+), and nitrite (+) achieved 87.6% (95% CI=84.2 to 90.5) sensitivity and 94.6% (95% CI=93.1 to 95.9) negative predictive value (NPV), with the decision tree identifying this combination as having the highest diagnostic utility (positive likelihood ratio (PLR) = 23.77, 95% CI=18.34 to 30.80). Conclusions: It seems that, integrating urine Gram staining with leucocyte esterase and nitrite improves UTI diagnosis in high-complexity emergency settings, reducing unnecessary urine cultures and antibiotic use while enhancing resource utilization and mitigating bacterial resistance.